Protecting group directed stereoselective reduction of an epi-inosose: efficient synthesis of epi-inositol - Patil, Madhuri T.; Krishnaswamy, Shobhana; Sarmah, Manash P.; Shashidhar, Mysore S. (Tetrahedron Letters, 2011)
A facile and high yielding synthesis of epi-inositol via stereoselective reduction of a pentaprotected epi-inosose is reported. Extent of stereoselectivity during the hydride reduction appears to depend on the ability of the substrate to complex with metal ions in the reducing agent. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Polyol; reduction; Stereoselective